ANALISIS YURIDIS TERHADAP PENOLAKAN VAKSINASI COVID-19 DITINJAU DARI HUKUM PIDANA (Suatu Analisis Terhadap Peraturan Daerah DKI Jakarta Nomor 2 Tahun 2020 Tentang Penanggulangan Covid-19 Di DKI Jakarta) - Sari Ramadhan, Renda Sumber; Purba, Nelvitia; Akhyar, Adil (Jurnal Ilmiah METADATA, 2021)
During the Covid-19 pandemic, the Government of Indonesia continued to work to deal with the spread of Covid-19. One of the efforts made by the Indonesian government is to carry out mass vaccinations that will be given free of charge to the public. The formulation of the problem in this thesis is how the legal arrangements for the implementation of the covid-19 vaccination are, how are the criminal sanctions against the refusal of the covid-19 vaccination in the DKI Jakarta Regional Regulation Number 2 of 2020 concerning Covid-19 Response in DKI Jakarta, what is the political policy of the legal sanctions for fines against citizens refusing to be vaccinated against COVID-19. This type of research is normative juridical, namely research based on legislation and empirical juridical. Data analysis was carried out qualitatively, which is a form of analysis that does not rely on numbers but on sentences. The results of the study indicate that the legal regulation for the implementation of the covid-19 vaccination is Presidential Regulation No. 14 of 2021 concerning Amendments to Presidential Regulation No. 99 of 2020 concerning Vaccine Procurement and Vaccination Implementation in the Context of Combating the 2019 Corona Virus Disease (Covid-19) Pandemic. That any person who has been designated as the target recipient of the Covid-19 Vaccine but refuses it may be subject to administrative sanctions. Criminal sanctions for refusing to vaccinate COVID-19 in DKI Jakarta Regional Regulation Number 2 of 2020 concerning Covid-19 Response in DKI Jakarta are dependent on the authority of each regional government. Sanctions can be given to the public to comply with the COVID-19 vaccination program. In principle, sanctions are the authority of the local government, and can be given so that the community obeys and participates in the vaccination program so that herd immunity can be achieved easily.